Invertebrate species richness in sandy beaches and rocky coast of Costa Rican North Pacific. - Sibaja-Cordero, Jeffrey Alejandro (2014)
This study summarizes published information on the number of invertebrate species reported for the intertidal zone of rocky coasts and sandy beaches of the North Pacific of Costa Rica. In addition, we present new data on macrofaunal species richness for several locations. There is a wide variation in the number of species reported, with mollusks, crustaceans, and polychaetes as the major contributors. The number of species depends on the faunal group and the sampled effort carried out in the previous studies of the intertidal zones, and during 2012. The data show that, taking into account all components of the community values, a range of 29-172 species were obtained from the rocky intertidal, and 5-15 species for the sandy beaches. We found a similar mean value for species richness between protected and not protected areas, because in both cases the range of values is wide. It is urgent to manage unprotected locations with high species richness that are exposed to impacts from development of human populations. Rev. Biol. Trop. 62 (Suppl. 4): 63-84. Epub 2014 Diciembre 01.